Implementasi Pembelajaran Nilai Agama dan Moral pada Anak Usia 4-5 Tahun selama Belajar dari Rumah - Maratus Solekah; Anik Lestariningrum; Linda Dwiyanti (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2021)
Education from early childhood is hampered by the pandemic that has hit so that learning processes must be carried out from home. Collaboration between teachers and parents is needed in improving aspects of child development, one of which is related to the habituation of cultivating moral religious values. The problems faced by not all parents support the implementation of the habituation while this institution has a uniqueness in the development of moral religious values while in school into a concept that emphasizes more time. To overcome this problem the teacher applies a variety of media and methods that will be carried out in collaboration with parents using fun activities. This research was conducted on 15 children in group A in RA Kusuma Mulia Mojosari, Kras District, Kediri Regency. The research method will be used as a qualitative study where data collection techniques from observation, interviews and documentation. Analysis of data using qualitative descriptive resultsobtained about the implementation of learning moral religious values in children aged 4-5 years using interactive media made by the teacher, which resulted in an increase in the indicators of the implementation of worship and the introduction of prayer times for 1 MB, 8 BSH children and 6 BSB children. Recommendations that can be given by the limitations of the media made by the teacher should be improved by making use of the surrounding environment so that aspects of religious moral values can also bedone like other aspects.